The Da'wah Message in an Indonesian Horror Film (Case Studies on Film Pengabdi Setan Using A Semiotics Model Roland Barthes) - Kiki Maulfi Hardiyanti; Muchlis Muchlis (Proceedings of International Conference on Da'wa and Communication, 2020)
The study described a horror film entitled Pengabdi Setan that describes a family that believes in Islam. However, it is said that the family did not follow the true Islamic Friday. With all the weird and creepy things that often happen to his family. In this case, one member of the family is the mother of the devil. It was done to produce offspring. In research for this thesis, researchers formulated the problem as "what message of Pengabdi Setan?" to address the problem, researchers employed the method and type of study of the semiotical analysis of Roland Barthes. The results of this study indicate that the messages of the da’wah in the hideous film Pengabdi Setan have three messages covering the aqidah, the Shari'ah message, and the morals message. These are summed up by the three theories of monology, dialogue, and speech. So, the three theories were used to obtain the message of Pengabdi Setan.